2008
DOI: 10.1186/1746-4269-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological uses of Erythrina senegalensis: a comparison of three areas in Mali, and a link between traditional knowledge and modern biological science

Abstract: This paper describes ethnopharmacological knowledge on the uses of Erythrina senegalensis DC (Fabaceae) in traditional medicine in three different areas (Dioila, Kolokani and Koutiala) in Mali. Data were collected using interviews of traditional healers selected randomly. The main reported diseases for which E. senegalensis was used by the traditional healers were amenorrhea, malaria, jaundice, infections, abortion, wound, and body pain (chest pain, back pain, abdominal pain etc). The fidelity level (which est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 27 publications
2
49
0
2
Order By: Relevance
“…The decoction of the stem bark of this tree is traditionally used by Bamoun population (Western Cameroon tribe) against liver disorders such as hepatitis and jaundice (Moundipa et al, 2002). In Mali, Erythrina senegalensis (ES) is used against several diseases and symptoms among which the main reported are malaria, jaundice, infections, gastrointestinal disorders, amenorrhea, dysmenorrhoea, sterility, onchocerchosis, body pain, abdominal pain and headache (Togola et al, 2008). Several compounds such as 2, 3 dihydroauriculatin (Taylor et al, 1986), Erybraedin A (Wanjala et al, 2002), isoflavonoids 6-8 diprenylgenistein (Oh et al, 1999) isolated from this plant have shown antimicrobial activities on various microbial species.…”
Section: Introductionmentioning
confidence: 98%
“…The decoction of the stem bark of this tree is traditionally used by Bamoun population (Western Cameroon tribe) against liver disorders such as hepatitis and jaundice (Moundipa et al, 2002). In Mali, Erythrina senegalensis (ES) is used against several diseases and symptoms among which the main reported are malaria, jaundice, infections, gastrointestinal disorders, amenorrhea, dysmenorrhoea, sterility, onchocerchosis, body pain, abdominal pain and headache (Togola et al, 2008). Several compounds such as 2, 3 dihydroauriculatin (Taylor et al, 1986), Erybraedin A (Wanjala et al, 2002), isoflavonoids 6-8 diprenylgenistein (Oh et al, 1999) isolated from this plant have shown antimicrobial activities on various microbial species.…”
Section: Introductionmentioning
confidence: 98%
“…Sores and wounds, pain, cough, tuberculosis and hepatitis were the most common indications, as demonstrated by their fidelity index (Table 4). Fidelity index (FI) is defined as (N p /N) × 100 where N p is the number of reported uses against any specific condition and N is the total number of uses reported (Togola et al, 2008). Stem bark and root, alone or in combination with other parts or other plants, were most frequently used.…”
Section: Resultsmentioning
confidence: 99%
“…This plant is applied in traditional medicine in the treatment of urinary bilharziosis (Togola et al 2008). The efficacy against juvenile S. mansoni in vivo remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…The 50 plants studied in the present work were selected based on results of a survey carried out between 1999 and 2005 in Northern Côte d'Ivoire on the use of medicinal plants for treating human parasitic diseases and associated discomforts (stomach ache, dysentery, diarrhoea (Koné 2005;Koné et al 2002Koné et al , 2005, animal parasitic diseases (Koné and Kamanzi Atindehou 2008) and on literature reports (Diehl et al 2004;Tra Bi et al 2005;Togola et al 2008;N'Guessan et al 2009 …”
Section: Plant Materialsmentioning
confidence: 99%